Compliance management and investment efficiency in state-owned enterprises: Evidence from China - Dengjin Zheng; Yan Xu; Yangyang Wenren (China Journal of Accounting Research, 2024)
Drawing on the implementation of the compliance management guidelines issued by China’s SASACs, we construct a quasi-natural experiment to examine the impact of the implementation of these guidelines on the investment efficiency of SOEs. The investment efficiency of SOEs is significantly improved after the implementation of the guidelines. The impact is more pronounced on SOEs with significant financing constraints, high financing requirements and intense competition in the product market. We also find that the guidelines improve efficiency investment by reducing management’s risk appetite, mitigating the Type I agency problems and enhancing the level of internal control. The conclusions indicate that compliance management is an important strategy for enhancing the investment efficiency of SOEs.